2016
DOI: 10.1177/0021934716653353
|View full text |Cite
|
Sign up to set email alerts
|

Leaders Wanted! The Skills Expected and Needed for a Successful 21st Century Historically Black College and University Presidency

Abstract: This study examines the 21st-century Historically Black College and University (HBCU) presidency. First, we gathered information on the skills needed for the 21st century HBCU president. Then, we examined the background of future HBCU presidents. Through an analysis and discussion of the responses of current HBCU presidents, trustees,1 and presidential search consultants, we determined what skills are pertinent for HBCU presidential hopefuls to attain. Lastly, we made recommendations, based on our findings, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This study seeks to better understand the modern contributions of HBCUs as described by their chief executive officers—HBCU presidents. Building on existing scholarship concerning the HBCU presidency (Freeman, Commodore, Gasman, & Carter, 2016; Freeman & Gasman, 2014; Gasman, 2011) and the contributions of larger, public land grant HBCUs (Esters & Strayhorn, 2013), this research focuses specifically on smaller, private HBCUs. Accordingly, this work expands the current literature concerning HBCUS and contributes to a more holistic understanding of this diverse group of institutions.…”
mentioning
confidence: 99%
“…This study seeks to better understand the modern contributions of HBCUs as described by their chief executive officers—HBCU presidents. Building on existing scholarship concerning the HBCU presidency (Freeman, Commodore, Gasman, & Carter, 2016; Freeman & Gasman, 2014; Gasman, 2011) and the contributions of larger, public land grant HBCUs (Esters & Strayhorn, 2013), this research focuses specifically on smaller, private HBCUs. Accordingly, this work expands the current literature concerning HBCUS and contributes to a more holistic understanding of this diverse group of institutions.…”
mentioning
confidence: 99%
“…They found that HBCU presidents tend to be recycled -meaning they move from one institution to the next, and that fairly few new leaders secure presidencies. Moreover, they found that although grooming of future presidents takes place, it is not systematic in nature (Freeman and Gasman, 2016). Freeman et al (2016) interviewed HBCU presidents, asking them what they thought the essential skills needed to become a president were.…”
Section: Msi Leadershipmentioning
confidence: 99%
“…Moreover, they found that although grooming of future presidents takes place, it is not systematic in nature (Freeman and Gasman, 2016). Freeman et al (2016) interviewed HBCU presidents, asking them what they thought the essential skills needed to become a president were. The seven skills mentioned the most by study participants included: vision, communication, fundraising, a disposition toward entrepreneurship, the ability to understand and negotiate with faculty, board management, and the ability to collaborate.…”
Section: Msi Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging scholarship on HBCUs examines more contemporary issues facing HBCU and their successes. There is a body of scholarship that examines the role of HBCUs presidents (e.g., Anderson et al, 2019;Freeman et al, 2016;Palmer & Freeman, 2019), since HBCUs president are often portrayed within scholarship and the Black community as symbolic figures. Some scholars even compare HBCUs presidents to that of leaders of Black Christian churches.…”
Section: Background Of Historically Black Colleges and Universitiesmentioning
confidence: 99%